A geometrical approach for network reconfiguration based loss minimization in distribution systems - Kashem, M (2001)
Network reconfiguration is one of the feasible methods for reducing the distribution network loss in which the power flow in the distribution network is altered by opening or closing the appropriate switches on the feeders. A geometrical approach for loss minimization is presented in this paper, in this method, each loop in a network is represented as a circle, which is derived from the relationship between the change of loss due to the branch-exchange and the power-flows in the branches. If there is no change of loss in the system, then all the circles touch each other at the (0,0) coordinate and the circles with no loss-change are called zero loss-change circles. The maximum loss-reduction loop in the network is identified by comparing the radii of all the zero loss-change circles. The corresponding loop of the largest zero loss-change circle gives the maximum loss reduction in the network. Then the possible branch-exchanges in the maximum loss-reduction loop are investigated by comparing the size of the circle for every branch-exchange. If the power losses are reduced due to a branch exchange, the size of the circle diminishes and hence the smallest circle gives the maximum loss-reduction and the corresponding branch-exchange is considered to be the best candidate for maximum loss-reduction. The performance of the proposed technique is tested on a 69-bus distribution system, and test results show that the method is found to reduce the computational effort and time considerably by reducing the numerous load-flow studies as compared to the method of Baran and Wu [IEEE Trans. Power Delivery, 4(2) (1989) 1401). (C) 2001 Elsevier Science Ltd. All rights reserved.